Evaluation of Antioxidant Activity and Total Phenolic Content in Bread Incorporated with Green Coffee Beans (GCB) - Kalthum Ibrahim, Ummi; Syafiqah Abd Wahab, Nurul; M. U. H., Suzihaque; Abd Hashib, Syafiza; Adawiya Abdul Aziz, Rabiatul (International Journal of Engineering and Technology, 2018)
Bioactive components in coffee had been scientifically proven to have a preventive role against various degenerative diseases. Green coffee is characterized by its unique composition and properties such as total phenolic content and antioxidant activity. The objective of this work was to investigate the effect of baking condition on the total phenolic content (TPC) and antioxidant activity (AA) of the bread incorporated with green coffee bean (GCB). Wheat flour was replaced with GCB flour at 1 to 5 wt% GCB flour over total of 200 g flour at varying baking conditions (baking temperature of 180, 200 and 220°C and baking time of 20, 30 and 40 minutes). TPC and AA of incorporated bread were determined using Follin-Ciocalteu reagent and DPPH assay, respectively. The results showed that the addition of GCB had significantly improved the total phenolic content and antioxidant activity of bread. The ideal baking condition that results in the highest of TPC and AA values was achieved at 180.1°C of baking temperature, 38.88 minutes of baking time and 5 wt% of GCB concentration.